2011
DOI: 10.1016/j.jsb.2011.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and crystalline calcium carbonate distribution in the tergite cuticle of moulting Porcellio scaber (Isopoda, Crustacea)

Abstract: a b s t r a c tThe main mineral components of the isopod cuticle consists of crystalline magnesium calcite and amorphous calcium carbonate. During moulting isopods moult first the posterior and then the anterior half of the body. In terrestrial species calcium carbonate is subject to resorption, storage and recycling in order to retain significant fractions of the mineral during the moulting cycle. We used synchrotron X-ray powder diffraction, elemental analysis and Raman spectroscopy to quantify the ACC/calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 49 publications
3
27
0
2
Order By: Relevance
“…To complement these fracture data, we also acquired Raman spectra in the impact regions. A Raman shift doublet near 3,000 cm À 1 corresponding to chitin, as well as minor bands in the range 1,300-1,400 cm À 1 also attributed to chitin 24 , were detected in the smasher dactyl club impact region but not in the spearer species (Fig. 7b).…”
Section: Microstructural Features and Preferred Fibre Orientationmentioning
confidence: 99%
“…To complement these fracture data, we also acquired Raman spectra in the impact regions. A Raman shift doublet near 3,000 cm À 1 corresponding to chitin, as well as minor bands in the range 1,300-1,400 cm À 1 also attributed to chitin 24 , were detected in the smasher dactyl club impact region but not in the spearer species (Fig. 7b).…”
Section: Microstructural Features and Preferred Fibre Orientationmentioning
confidence: 99%
“…than Cuif et al (2011) for Galaxea fascicularis. Nothdurft and Webb (2007) observed that a vertical extension of 384 µm equals 36 µm in lateral growth by tracking growth lines in a skeletal rod of Porites lobata. This vertical distance was deposited within 12 days (derived from mean growth rates for this species; see Nothdurft and Webb, 2007) and equals a lateral growth of 3 µm per day.…”
Section: Growth Layersmentioning
confidence: 99%
“…They are arranged along the central axis and surrounded by fibers that represent the bulk of the skeleton (e.g. Cohen and McConnaughey, 2003;Nothdurft and Webb, 2007). These different skeletal morphological levels reflect the complex arrangement of coral skeletal elements and are specific for each taxon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations